THE ROLE OF LABORATORY BIOMARKERS IN PREDICTING THE EFFICIENCY OF RITUXIMAB THERAPY FOR RHEUMATOID ARTHRITIS: NEW EVIDENCE - A. S. Avdeeva; D. A. Kusevich (Научно-практическая ревматология, 2017)
Rheumatoid arthritis (RA) is the most common and severe chronic joint inflammatory disease leading to early disability and shorter lifespan in patients. A number of studies have demonstrated that short-term and long-term prognosis of the disease is much more favorable in achieving remission in the early stages of the disease; however, the efficacy of drugs varies widely from patient to patient, which is due to the heterogeneity of the disease itself and to a number of other causes. In this connection, the problem of searching for biomarkers that allow the personalized choice of a treatment regimen in each specific case remains relevant as before.Rituximab (RTM) that is a chimeric monoclonal antibodies against CD20 membrane antigen of B cells causing the depletion of various B lymphocyte subpopulations is one of the effective and safe drugs used to treat RA. Compared to other biological agents, RTM has a long-term efficacy of one treatment cycle, which persists for 6 months or more. The current literature presents a large amount of data on the role of cellular and molecular biomarkers in predicting the efficiency of RTM therapy for RA, some of which are considered in this review.